House prices and credit as transmission channels of monetary policy to inequality: evidence from OECD countries - Vale, S. (8th UECE Conference on Economic and Financial Adjustments, ISEG/UL, 2020)
Monetary policy is conceived to stabilize inflation and the output gap, however, its actions end up affecting the income and wealth distributions, an aspect that has been gaining relevance in the literature. This paper employs a panel vector autoregressive model to assess the OECD economies over the period comprised between 1995Q1 and 2017Q4. We seek to quantify the distributional effects of monetary policy shocks through the transmission channels of housing prices and households’ debt, the two sides of households’ balance sheets at a macroeconomic level. The analysis of the impulse-response functions and variance decomposition indicates that a contractionary monetary policy increases the Gini coefficient and that a rise in house prices will further increase inequality. The results are robust to different model specifications.